Efektifitas Minuman Ritemjeri (Sari Tempe Jelly Seledri) Terhadap Tekanan Darah Pasien Hipertensi di Puskesmas Punti Kayu Kota Palembang - Misnawati, Misnawati; Muzakar, Muzakar; Susanto, Eddy; Sadiq, Ahmad; Podojoyo, Podojoyo (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2021)
Background : Hypertension or high blood pressure is a condition which is characterized by an increase in systolic blood pressure ≥ 140 mmHg and diastolic blood pressure ≥ 90 mmHg at two measurements with an interval of five minutes in a state of sufficient rest or calm. One of the non-pharmacological therapies that can help lower blood pressure is by utilizing foods that contain high potassium and Apigenin namely tempe and celery. Purpose : To determine the effect of tempe juice and celery jelly on reducing blood pressure of hypertension sufferers at the Palembang Punti Kayu Health Center.Method : This study was a quasi-experimental study with a pre-test and post-test with control group design. The subjects of this study were 60 people with hypertension at the Punti Kayu Health Center who were willing and fulfilled the inclusion and exclusion criteria. Data analysis uses t-dependent and t-independent tests. Results : The study showed that there was an average decrease in systolic and diastolic blood pressure in the treatment group of 9,517 mmHg and 10,282 mmHg (p-value = 0,000 and p-value = 0,000). Whereas in the comparison group the mean decrease in systolic and diastolic blood pressure was 6,94 mmHg and 14,060 mmHg (p-value = 0.000 and p-value = 0,000). T-independent statistical test results for systolic blood pressure in the treatment and comparison groups obtained p-value 0.037 (p <0.05) and diastolic blood pressure obtained p-value 0.046 (p <0.05). Conclusion : There is an effect of giving tempe juice and celery jelly on the blood pressure of hypertension sufferers in Palembang Punti Kayu Health Center.